Research on the design of somatosensory interactive games for autistic children based on art therapy - Huili, She; Xiaolin, Cao; Guangsen, Guo; Yu, Jiang; Yu, Liu; Wenpei, Zhang (Frontiers in Psychiatry, 2023)
There is no targeted drug treatment for autistic children. Educational intervention and rehabilitation are the main ways to improve the ability development of autistic children. However, there are great differences in the individual symptoms and abilities. It is an urgent need for educators, practitioners and parents of autistic children to find effective ways to improve their cognitive, social and motor abilities.The author cooperates with the therapist to study and design the somatosensory interaction game for autistic children, which is a formal attempt of art therapy on the treatment tool, with the purpose of studying an effective and safe art intervention method. In order to verify the effect, the author recruited 26 children with mild or moderate autism for a six-week empirical evaluation, and the participants were randomly assigned. Among them, 13 participants participated in the art therapy of the proposed somatosensory game group (the experimental group), and 13 participants Participated the traditional picture book group (the control group) that improved the emotion, cognition and skills of children, and the design style was more popular with children. The aesthetic design in the picture book could have an intervention effect on the participants, and its artistic effect could serve as an effective reference for the interface design of the game group. The results showed that the two groups had a significant impact on the participants in different aspects. The game group improved not only in terms of concentration and special ability, but also in terms of physical coordination and activity enhancement, It is inferred that the core factors of game therapy are subintervention, interaction and feedback, icon design and color matching system; The picture book group has significant improvement in interpersonal relationship guidance and language learning and communication. The results show that it is necessary to take more comprehensive and richer preliminary research on the development of treatment products for autistic children. Because picture book education requires children's initial concentration, it is found that picture book therapy has high requirements for teachers' classroom control and relatively strict requirements for picture book content,and play therapy can be a good complement to these problems.